Openness to adopting evidence-based practice in public substance use treatment in South Africa using task shifting: Caseload size matters. Issue 2 (3rd April 2018) - Magidson, Jessica F.; Lee, Jasper S.; Johnson, Kim; Burnhams, Warren; Koch, J. Randy; Manderscheid, Ron; Myers, Bronwyn
ABSTRACT: Background : In response to the lack of coverage for substance use treatment in the Western Cape province of South Africa, the local government expanded funding for evidence-based practices (EBPs) for treating substance use. Yet, little is known about provider and staff attitudes towards adopting EBPs in this setting, which is particularly relevant in this context where task shifting clinical care increases demands on paraprofessional providers. This study aimed to (1) assess attitudes towards adopting EBPs among a range of staff working in substance use treatment in Cape Town using a task shifting model; and (2) evaluate factors associated with openness towards adopting EBPs in this setting. Methods : Staff ( n = 87) were recruited from 11 substance use treatment clinics. Demographics and job-related characteristics were assessed. Staff perceptions of organizational factors were assessed using the TCU Organizational Readiness for Change (ORC) scale. The dependent variable, attitudes towards adopting EBPs, was assessed using the Evidence-Based Practice Attitude Scale (EBPAS). Results : This study is one of the first to administer the EBPAS in South Africa and found good internal consistency (total score: α = .82). In a multivariable model adjusting for site and factors associated with EBPAS total score at the bivariate level, only smaller caseload size was associated with greater openness to adopting EBPs (B = 1.61, SE = .73; t = 2.21; p <.05). Conclusions : As pressure to scale up implementation of EBPs in South African substance use treatment services intensifies, additional efforts are needed to understand barriers to adopt EBPs in this setting. Supporting staff adoption of EBPs in resource-limited settings may require additional resources to limit staff caseloads in the context of task shifting.